Records Committee review for rare bird sighting of Lesser Black-backed Gull at Saylorville Reservoir, 1987 - Armstrong, Eugeneet al (1987)
Records Committee review for a Lesser Black-backed Gull at Saylorville Reservoir in Polk County, IA on December 29, 1987. Includes a record review document with votes and two documentation forms submitted to the committee. Epson - sheet feed